Investigation of aerosol direct radiative forcing during a dust storm using a regional climate model over Turkiye - Yavuz, Elif; Kuzu, Levent; Ugurdogan, Serdar; Saral, Arslan (YILDIZ TECHNICAL UNIV, 2023)
Dust particles originating from arid zones can be transported long distances and change the radiation budget. Understanding atmospheric aerosols and their radiative forcing is important to determine their global and regional climate effects. The aim of this study is to simulate the dust transport event that occurred on March 22, 2018, using RegCM-4.5 and investigate the radiative forcing effect of Saharan dust particles. The model was run with the 4 dust bin chemistry option and the direct effect of aerosols on the regional radiation balance was investigated. Validation of the model was made by a comparison between simulated aerosol optical depth (AOD) and MODIS satellite data. The radiative forcing at the top and surface was calculated at all sky conditions. During the dust episode, the shortwave radiative forcing was ranging between -3 and -50 W/m(2) at surface and - 2 and -22 W/m(2) at top of atmosphere while the longwave radiative forcing was between 0.5 and 8 W/m(2) at surface and 0.2 and 2 W/m(2) at top of atmosphere over Turkiye. In Istanbul it produced a cooling up to -18 W/m(2) at surface and -9 W/m(2) at top of atmosphere, a warming up to 3.5 W/m(2) at surface and 0.6 W/m(2) at top of atmosphere.
Keywords: Dust Transport; Regional Climate Model; Radiative Forcing; Longwave Radiation; Shortwave Radiation; MINERAL DUST; IMPACT; Engineering